2016
DOI: 10.3892/ol.2016.5062
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis and treatment of gastrointestinal neuroendocrine tumors

Abstract: Abstract. The aim of the present retrospective analysis on the macroscopic appearance and pathological characteristics of gastrointestinal neuroendocrine tumors (NETs) was to investigate methods for their early diagnosis and treatment. A total of 78 patients were divided into submucosal NET and deeper invasion NET groups, according to the depth of tumor invasion exhibited by the patients. The clinicopathological characteristics and survival time of the NET patients were analyzed and compared. The pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Neuroendocrine tumors (NETs) are rare tumors with a relative incidence of 2% of all neoplasms and are most commonly found in the gastroenteropancreatic tract [ 1 ]. The absolute incidence of these rare neoplasms has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroendocrine tumors (NETs) are rare tumors with a relative incidence of 2% of all neoplasms and are most commonly found in the gastroenteropancreatic tract [ 1 ]. The absolute incidence of these rare neoplasms has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute incidence of these rare neoplasms has increased in recent years. This is mainly due to the improved diagnostics and increasing knowledge about these tumors [ 1 , 2 ]. The clinical outcome of patients with NETs depends on several factors, such as location and resectability of the tumor, Ki67 expression, which determines grading, and finally staging [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal neuroendocrine tumors (NETs) have a low, but gradually increasing, incidence worldwide[1]. Specifically, the overall prognosis for patients with gastrointestinal NETs has improved and has been favorable[2], but some investigators have reported 5-year survival rates of patients with NET G1 of approximately 80%[3]. Although few patients with liver metastases[4-7] and one with fatal GP[6] have been reported, GP shows a benign course more frequently than NET G1.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroendocrine tumors (NETs), once considered a rare malignancy, have started to become a more prevalent cancer in the United States (US) [1]. The most common location of NETs is in the gastrointestinal (GI) system [1-3]. In the US, the incidence is increasing, with a seven-fold increase over the past 35 years [1].…”
Section: Introductionmentioning
confidence: 99%
“…The most common location of NETs is in the gastrointestinal (GI) system [1-3]. In the US, the incidence is increasing, with a seven-fold increase over the past 35 years [1]. Prior studies that have evaluated the incidence of NETs have used the National Cancer Institute’s (NCI) Surveillance, Epidemiology, and End Results (SEER) program.…”
Section: Introductionmentioning
confidence: 99%